2007
DOI: 10.1093/jb/mvm143
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Mitochondrial Calpains

Abstract: Calpains are considered to be cytoplasmic enzymes, although several studies have shown that calpain-like protease activities also exist in mitochondria. We partially purified mitochondrial calpain from swine liver mitochondria and characterized. Only one type of mitochondrial calpain was detected by the column chromatographies. The mitochondrial calpain was stained with anti-mu-calpain and calpain small subunit antibodies. The susceptibility of mitochondrial calpain to calpain inhibitors and the optimum pH dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 37 publications
2
72
0
Order By: Relevance
“…Furthermore, mitochondrial μ-calpain isolated from the rat cerebral cortex and from SH-SY5Y neuroblastoma cells has a mitochondrial targeting sequence in its N-terminal region [24]. Additionally, relatively high calpain activity is detected in both the mitochondrial IMS and matrix, as well as in the cytosol, in swine liver [19]. In bovine pulmonary smooth muscle mitochondria, μ-calpain in the IMS cleaves NCX on the IM after Ca 2+ ionophore treatment [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, mitochondrial μ-calpain isolated from the rat cerebral cortex and from SH-SY5Y neuroblastoma cells has a mitochondrial targeting sequence in its N-terminal region [24]. Additionally, relatively high calpain activity is detected in both the mitochondrial IMS and matrix, as well as in the cytosol, in swine liver [19]. In bovine pulmonary smooth muscle mitochondria, μ-calpain in the IMS cleaves NCX on the IM after Ca 2+ ionophore treatment [14].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac mitochondria were isolated from 8-week-old male Sprague-Dawley rats using a Mitochondria Isolation Kit for Tissue and Cultured Cells (#K288-50; BioVision, Milpitas, CA), and the isolated mitochondria underwent subfractionation according to Ozaki et al [19]. Briefly, the isolated mitochondria were suspended in 2 volumes of 20 mM of potassium phosphate buffer containing 0.2 mg/ml of bovine serum albumin (BSA; Sigma-Aldrich, St. Louis, MO) at pH 7.4 and allowed to stand at 4°C for 1 h. The suspension was centrifuged at 3000 ×g for 10 min, and the supernatant was centrifuged at 105,000 ×g for 30 min.…”
Section: Isolation and Subfractionation Of Mitochondriamentioning
confidence: 99%
“…They detected calpain 1 in the cytosol, but not in the mitochondrial fractions, and noted that calpain 1 does not contain an identifiable mitochondrial targeting signal. Ozaki et al (50) recently identified a mitochondrial calpain in both the IMS and matrix of swine liver mitochondria, but concluded that this calpain was distinct from the m-and -calpains based on size, enzymatic activity, and pH optimum. In contrast, Cao et al (69) found calpain 1 in the IMS of rat brain mitochondria, but did not evaluate the localization of the small calpain subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Tel/Fax: +81-19-621-6157; E-mail: yamashit@iwate-u.ac.jp Abbreviations: GOT, glutamate oxaloacetate transaminase; MDH, malate dehydrogenase described. 23,24) Mitochondrial intermembrane space (IMS) and matrix fractions of the kidney and liver were prepared from 10 SpragueDawley rats (8 weeks old). The rat kidneys and liver were washed and homogenized with buffer A (20 mM Tris-HCl pH 7.5, containing 1 mM EDTA, 1 mM EGTA, 5 mM 2-mercaptoethanol, 150 mM NaCl, 0.25 M sucrose, and complete protease inhibitor cocktail, Roche Applied Science, Basel, Switzerland).…”
Section: Methodsmentioning
confidence: 99%